Observational study to determine the proportion of types of congenital heart diseases in high-risk pregnancies with detailed prenatal echocardiography - ., Balakrishna; Gehlot, Ramanand; Chaturvedy, Kirti; Rajpurohit, Dalpat Singh; Chandel, Manvika; Kumawat, Nauratmal; Rathod, Viram Singh; Pareek, Deepak; Patel, Rughnath; Sheoran, Pradeesh; Mishra, Divyangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Specific factors that increases a mother’s risk of carrying a fetus with CHD, with the use of extended views in fetal echocardiography in addition to basic standard views there is increased detection of CHDs. Purpose of study current study was to investigate the role of fetal echocardiography in prenatal diagnosis of the congenital heart diseases in high-risk pregnancies between 18-36 weeks of gestational age and to determine the proportion of occurrences of different types of CHDs in and high-risk group. Methods: Observational study with consecutive sampling 880 subjects. Study done in department of radiodiagnosis, SNMC, Jodhpur, Rajasthan Results: With use of basic standard views, extended views and 3D views total 27 cases were detected out of all 880 subjects, which is significant statistically. Many CHDs which can be missed by the standard views, can be more efficiently detected with use of extended views in the fetal echocardiography. Conclusions: Most common type of CHD was found to be VSD and hypoplastic left heart syndrome.